(untitled) (REMUNOM, 2025)
The internship is one of the most important parts of a student’s academic training, as it is the moment when theoretical knowledge is transformed into practice. The aim of this work was to describe the experiences acquired during the Supervised Curricular Internship (ECS) in Physical Education classes, in high school classes. This article is a descriptive experience report. It lasted 11 months and was divided into theoretical-practical, practical with 20 classes taught and dialogue with society, developed in a public educational institution located in the interior of Goiás. The results showed the importance of the internship in the day-to-day life of the school, and how methodological interventions influence student performance throughout the lessons, as well as the importance of having quality infrastructure and teaching materials for practical activities. It is possible to conclude that the supervised internship is a valuable stage in teacher training, building knowledge and know-how to face new challenges in the teaching profession. In addition, experiences like these should be exposed, seeking to report more realities about the discipline of education in school environments.